Bug Blonsky and his very long list of don'ts - Redmond, E. S. (Somerville, Massachusetts : Candlewick Press, 2018)
The easily distracted Bug makes a list of all the things he should'nt do after a series of choices land him in a heap of trouble.
Keywords: Behavior -- Fiction; Schools -- Fiction; Human behavior -- Fiction; School stories; Humorous fiction; Humorous fiction